The Phenomena of Social Media Interaction on Global Muslim Identity Construction - Isbahi, Muhammad Baiqun (Proceedings of International Conference on Da'wa and Communication, 2019)
The growth interaction of social media has become a global phenomenon. Recently, internet usage throughout the world has led to the popularity of social network sites. Facebook, Twitter, Instagram, and YouTube are the common websites shaped cooperative structures wherein the human digital crowd is encouraged proactively. The increasing interest in this means of communication technology has significant impacts on the social landscapes of global affairs and physical social life. Both of these factors make people play certain characters in the social arena. The Social Network is gaining more and more importance today and has a deeper impact on society as to the traditional media. Social media enables identity expression, exploration, and experimentation; something natural for the human experience. It is the agencies in real life, which provide a source of names for different sectors, that inspire the internet communities and the interactions they make within themselves. It is essential to comprehend the motives of agencies to have an understanding of the group interactions on social platforms. However, (Especially,) the perception of global Muslim worldviews are being challenged by these means of the information revolution. Therefore, the purpose of this paper is to examine practical aspects of social media interaction on the global Muslim identity construction. Global Muslims is viewed on the existing relationship and critics of their civilization are also made in this work. Qualitative method is applied in conducting the work which enables authors to arrive at indisputable logical facts.